“A GENTE DORMIU TRAVESSIA E ACORDOU PARQUE DO MIRADOR”: resistências e conflitos socioespaciais em uma região de expansão de soja nas chapadas do Cerrado sul do Maranhão - BATISTA, Carlos dos Santos (2021)
This paper aims to study the forms of resistance of peasant communities and the impacts (environmental and/or social) on their territories, against the creation of the Mirador State Park - Mirador - MA. Created by state decree No. 7.641 on June 4, 1980, Mirador State Park is located in the geographical mesoregion of southern Maranhão and has taken over different peasant territories. In these terms, it has become imperative to analyze the different reasons that resulted in the creation of the integral conservation unit, which only admits indirect uses of nature, as well as the resulting conflicts. As well as the consequences of the State's failure to regularize the land tenure of peasant communities. Since the institutionalization of an environmental conservation unit of the integral type, which regulates and limits the presence of these groups since then, the restriction of access and use of territory by the communities became subordinate to state action. This territory, before being transformed into a state park, was identified as the Crossing of Mirador/Tapicuru, which, a priori, serves to designate a specific region between the sources of the Itapecuru and Alpercatas rivers, deriving the idea of crossing Mirador/Tapicuru by peasant communities. Furthermore, the region concentrates the springs of the Itapecuru river basin, one of the most important for the supply of the state. From this situation, it was necessary to think about parallel issues such as the restriction of access and use of territory by the communities since the institutionalization of an environmental conservation unit of the integral type that regulates and limits the presence of these groups since then. Underlying the conflict between the State and peasant communities, the emergence of agricultural projects is problematized in the redimensioning of the cartographic limits, together with the advance in the surroundings and over the areas of the Mirador State Park. For the theoretical and methodological development, we use the dialectical method, because we understand that capturing the distinct scales of production of life is a continuous movement of construction and reconstruction of events and moments in a given space and time. Finally, to think how the conflicts arising from the transformation of the territory used (Mirador/Tapicuru Crossing), into an integral protection conservation unit reveals the nature of the disputes for the use of territory by the most distinct agents.